2015
DOI: 10.2174/1874120701509010250
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Vascular Surgery Related Infection

Abstract: Surgical site infection (SSI) is an important component of infections acquired from hospital. The most significant feature of vascular surgery different from other surgeries is frequent application of artificial grafts. Once SSI occurs after vascular operations with grafts, it might results in a serious disaster. Staphylococcus aureus and coagulase-negative Staphylococcus are the most common pathogenic bacteria for SSI after vascular surgery. Although SSI in vascular surgery often lacks of typical clinical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Infections in artificial veins can sometimes lead to its replacement 21 or even serious organ damage 20 . The epidermis is the primary source of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Infections in artificial veins can sometimes lead to its replacement 21 or even serious organ damage 20 . The epidermis is the primary source of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Although a major source for vascular surgery infections is by bacteria transference with vascular graft tissue, 44 patients undergoing non-implant surgery -as with most surgical procedures -are also prone to infection via the surgical procedure. In a recent (non-randomised comparative) study, the use of Leukomed Sorbact was shown to be an effective treatment in this indication.…”
Section: Vascular Surgerymentioning
confidence: 99%
“…Periprosthetic joint infections (PJIs) can be a devastating complication resulting from some arthroplasties and can involve infection of both the soft tissue surrounding the prosthetic implant as well as the inside of the bone in severe cases [ 1 ]. To mitigate the development of and to treat PJIs, antibiotic-laden poly(methyl methacrylate) (PMMA) bone cement is often utilized where it is either directly implanted in the bone (i.e., arthroplasty fixation) or in the form of beads that are embedded into the surrounding infected soft tissue to locally deliver antibiotics [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. When antibiotic-laden PMMA is directly implanted into the bone, there is a unique challenge to administer additional antibiotic doses into the implanted PMMA if the infection is prolonged.…”
Section: Introductionmentioning
confidence: 99%